A formação do formador: sujeitos formadores a Sujeitos em formação - Gomes, Fabrícia Barêa (2008)
The subject of this research is the teachers education, more specifically the continuity education, oferred to teachers of primary school level. The actual tendency of educational politics increased significantly the offer of educational programs on work. In order to contribute with the discussions related to the range of these programs on the pedagogical practice of teachers responsible for alphabetizing, this work aimed to investigate: which is the compatibility between alphabetizing teachers and the procedures defined by one of the continued educational programs of those teachers implemented by the state public school network in São Paulo. For different reasons, we have considered convenient and logical to choose teachers who worked on the initial terms and that they were also ex-students aproved and certified on the referred program. We have performed different procedures for collecting data to prepare this work, such as: interviews, local observations and documental analysis. The research was restricted to only one education directory of São Paulo, located at Least Region. The results analysis has indicated a great difficulty faced by the teachers to join the principles defined in the program, leading us to investigate the process of continuity education and the conditions they are implemented, considering the distortions presented bewteen the continuity education politics and its implementation on a day-to-day basis